2002
DOI: 10.1002/art.10445
|View full text |Cite
|
Sign up to set email alerts
|

Diminished peripheral blood memory B cells and accumulation of memory B cells in the salivary glands of patients with Sjögren's syndrome

Abstract: Objective. To delineate the mechanism of the abnormalities in B cell biology found in patients with primary Sjögren's syndrome (SS).Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
198
0
12

Year Published

2003
2003
2006
2006

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 246 publications
(243 citation statements)
references
References 56 publications
33
198
0
12
Order By: Relevance
“…Recent studies have shown disturbances in peripheral B cell populations in primary SS, with significantly enhanced CD27Ϫ naive and diminished CD27ϩ memory B cells (6,8,9). This was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Recent studies have shown disturbances in peripheral B cell populations in primary SS, with significantly enhanced CD27Ϫ naive and diminished CD27ϩ memory B cells (6,8,9). This was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of peripheral CD27ϩ,CD19ϩ memory B cells was significantly reduced in patients with primary SS compared with healthy control subjects (mean Ϯ SD 13.3 Ϯ 12.3% versus 25.6 Ϯ 7.2%; P Յ 0.0014), whereas the frequency of CD19ϩ,CD27Ϫ naive B cells was significantly enhanced in patients with primary SS (mean Ϯ SD 86.1 Ϯ 12.0% versus 74.4 Ϯ 7.2%; P Յ 0.0014) as reported previously (6,8,9). To ensure that these alterations in patients with primary SS did not further influence the analyses, either CD19ϩ,CD27Ϫ or CD19ϩ,CD27ϩ B cells were gated, and the chemokine receptor expression was subsequently analyzed within each subpopulation ( Figures 1A and B).…”
Section: Chemokine Receptors On B Cells In Primary Ss 2111supporting
confidence: 84%
See 3 more Smart Citations